Imaging of osteonecrosis of the femoral head - Azzali, Emanuele; Milanese, Gialuca; Martella, Ilenia; Ruggirello, Margherita; Seletti, Valeria; Ganazzoli, Chiara; Bono, Nicola Emanuele; Negri, Francesco; Pogliacomi, Francesco; De Filippo, Massimo (Acta Biomedica Atenei Parmensis, 2016)
Osteonecrosis of the femoral head is a common disease affecting both children and adults causing acute hip pain and functional impairment. Among the various techniques allowing a correct diagnosis, MRI represents the gold standard for an early detection, the latter being useful for a positive outcome. The purpose of this review is to describe the imaging findings of the osteonecrosis of the femoral head.